Biotechnological convergence: biodiversity and bioprospecting as a conservation strategy - Betancur P., Jhon Fredy (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Biological diversity, also known as biodiversity, refers to the variety of animal, plant, and microorganism species present in a region or country. Biodiversity is a key indicator used to characterize nations based on the number and variety of species that inhabit a certain geographical area. For Colombia, the Convention on Biological Diversity was established to promote the sustainable use of biodiversity and ensure the fair and equitable distribution of benefits derived from its commercial exploitation, as stated in Article 1. In this context, biodiversity is defined in a general manner, encompassing not only plants, animals, and microorganisms, but also all the genetic diversity present among different populations of the same species. Bioprospecting is a method for using natural resources in a responsible, rational, and sustainable manner. It involves searching and exploring biodiversity, particularly living organisms such as plants, microorganisms, and animals, to identify chemical compounds, biomolecules, or genes that can be used to create products for industries such as food, biotechnology, pharmaceuticals, and agriculture.